2019
DOI: 10.1002/asna.201913610
|View full text |Cite
|
Sign up to set email alerts
|

Optical precursors to X‐ray binary outbursts

Abstract: Disc instability models predict that for X-ray binaries in quiescence, there should be a brightening of the optical flux prior to an X-ray outburst. Tracking the X-ray variations of X-ray binaries in quiescence is generally not possible, so optical monitoring provides the best means to measure the mass accretion rate variability between outbursts, and to identify the beginning stages of new outbursts. With our regular Faulkes Telescope/Las Cumbres Observatory (LCO) monitoring we are routinely detecting the opt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 28 publications
0
38
0
Order By: Relevance
“…MAXI J1348-630 was discovered as a bright X-ray transient on 2019 January 26 (Yatabe et al 2019) by the MAXI monitor onboard the International Space Station (Matsuoka et al 2009) and, thanks to immediate and intense multiwavelength follow-up observations, it was subsequently identified as a BH candidate (Chen et al 2019;Denisenko et al 2019;Kennea & Negoro 2019;Nesci & Fiocchi 2019;Sanna et al 2019;Russell, Baglio & Lewis 2019b;Russell et al 2019c). MAXI J1348-630 displayed a typical outburst that was followed by four reported subsequent hard state re-flares (Russell et al (Al Yazeedi et al 2019;Negoro et al 2019;Russell et al 2019d;Carotenuto et al 2020;Pirbhoy et al 2020;Shimomukai et al 2020;Zhang et al 2020b). While currently, no information is available on the BH inclination, mass, spin and companion star, it has been possible to measure a source distance D = 2.2 +0.5 −0.6 kpc (Chauhan et al 2021) from observations of H I absorption carried out with the Australian Square Kilometre Array Pathfinder (ASKAP) and with MeerKAT.…”
Section: Maxi J1348-630mentioning
confidence: 99%
“…MAXI J1348-630 was discovered as a bright X-ray transient on 2019 January 26 (Yatabe et al 2019) by the MAXI monitor onboard the International Space Station (Matsuoka et al 2009) and, thanks to immediate and intense multiwavelength follow-up observations, it was subsequently identified as a BH candidate (Chen et al 2019;Denisenko et al 2019;Kennea & Negoro 2019;Nesci & Fiocchi 2019;Sanna et al 2019;Russell, Baglio & Lewis 2019b;Russell et al 2019c). MAXI J1348-630 displayed a typical outburst that was followed by four reported subsequent hard state re-flares (Russell et al (Al Yazeedi et al 2019;Negoro et al 2019;Russell et al 2019d;Carotenuto et al 2020;Pirbhoy et al 2020;Shimomukai et al 2020;Zhang et al 2020b). While currently, no information is available on the BH inclination, mass, spin and companion star, it has been possible to measure a source distance D = 2.2 +0.5 −0.6 kpc (Chauhan et al 2021) from observations of H I absorption carried out with the Australian Square Kilometre Array Pathfinder (ASKAP) and with MeerKAT.…”
Section: Maxi J1348-630mentioning
confidence: 99%
“…On 2019 July 30, Russell et al (2019b) reported a brightening in the optical i′-band from the direction of SAXJ1808, which is often a precursor to a full X-ray outburst (Russell et al 2019a). Although this predictor had not previously been tested for SAXJ1808 specifically, various X-ray, UV, and radio observatories were triggered to monitor SAXJ1808 over the following days.…”
Section: Introductionmentioning
confidence: 99%
“…The optical monitoring data in B, V, R, i bands (B, V, R in the Vega system and i in the AB system) were taken with the 2-m Faulkes Telescope South (at Siding Spring, Australia) and Las Cumbres Observatory (LCO) 1-m robotic telescopes in Chile, South Africa and Australia (see 50,51 ). The Faulkes/LCO magnitudes were calculated using the 'X-ray Binary New Early Warning System' (XB-NEWS; see 52,53 for details) data analysis pipeline. To estimate the optical flux of SAX J1808.…”
Section: Methodsmentioning
confidence: 99%